2021
DOI: 10.21203/rs.3.rs-1004063/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Course of Biotinidase Activities After Neonatal Period in The Screened Newborns and Consequences of The Concordance With Their Genotypes.

Abstract: Background/aim: Biotinidase deficiency (BTD) is characterized by broad genotypic variants and unsteady biotinidase activity. Increasing enzyme activity and maturation throughout childhood. This study aims to reveal the course of biotinidase activities in a long-term follow-up period and concordance with their genotypes .Participants/Methods: A total of 1,773 biotinidase enzyme (BT) activity measurements were performed in 711 newborns with variants in the BTD gene over a 4-year follow-up period. Biochemical phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…[2] There have been many studies to date evaluating the relationship between genotypes and phenotypes in biotinidase enzyme de ciency, however biotinidase enzyme activity measurements were made only once or twice in most of them. [2][3][4][5][6][7][8][9][10][11][12][13] As biotinidase enzyme activity measurements may be affected by such external factors as age, prematurity, neonatal jaundice and the temperature of the sample during storage or transport, [1; 4; 14; 15] it is suggested that a diagnosis of biotinidase enzyme de ciency should be based on multiple measurements of plasma biotinidase enzyme activity. [4] We believe that repeated measurement of biotinidase enzyme activity during the clinical follow-up of patients with biotinidase enzyme de ciency can lead to a better evaluation of the genotype and phenotype relationship and the exclusion of external factors.…”
Section: Introductionmentioning
confidence: 99%
“…[2] There have been many studies to date evaluating the relationship between genotypes and phenotypes in biotinidase enzyme de ciency, however biotinidase enzyme activity measurements were made only once or twice in most of them. [2][3][4][5][6][7][8][9][10][11][12][13] As biotinidase enzyme activity measurements may be affected by such external factors as age, prematurity, neonatal jaundice and the temperature of the sample during storage or transport, [1; 4; 14; 15] it is suggested that a diagnosis of biotinidase enzyme de ciency should be based on multiple measurements of plasma biotinidase enzyme activity. [4] We believe that repeated measurement of biotinidase enzyme activity during the clinical follow-up of patients with biotinidase enzyme de ciency can lead to a better evaluation of the genotype and phenotype relationship and the exclusion of external factors.…”
Section: Introductionmentioning
confidence: 99%